2010
DOI: 10.1002/jcb.22468
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of integrins α3β1 and α5β1 and glycoprotein IIb in megakaryocyte‐induced osteoblast proliferation

Abstract: As the prevalence of osteoporosis is expected to increase over the next few decades, the development of novel therapeutic strategies to combat this disorder becomes clinically imperative. These efforts draw extensively from an expanding body of knowledge pertaining to the physiologic mechanisms of skeletal homeostasis. To this body of knowledge, we contribute that cells of hematopoietic lineage may play a crucial role in balancing osteoblastic bone formation against osteoclastic resorption. Specifically, our l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 40 publications
4
45
1
Order By: Relevance
“…We previously reported that OB cell number is significantly increased when OBs are co-cultured with MKs in vitro (1,2,4). In addition, our studies reveal that MKs stimulate OB proliferation in part through direct cell-cell contact and via a mechanism that requires integrin engagement (5). Furthermore, in GATA-1-deficient mice in which MK numbers are increased, bone mineral density is increased (6), and histological evaluation reveals an increase in OB numbers on trabecular surfaces, suggesting that MKs stimulate OB proliferation in vivo.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…We previously reported that OB cell number is significantly increased when OBs are co-cultured with MKs in vitro (1,2,4). In addition, our studies reveal that MKs stimulate OB proliferation in part through direct cell-cell contact and via a mechanism that requires integrin engagement (5). Furthermore, in GATA-1-deficient mice in which MK numbers are increased, bone mineral density is increased (6), and histological evaluation reveals an increase in OB numbers on trabecular surfaces, suggesting that MKs stimulate OB proliferation in vivo.…”
supporting
confidence: 52%
“…MKs are responsible for the production of thrombocytes, which are necessary for blood clotting. Although the mechanism has yet to be fully elucidated, a growing body of evidence also suggests that MKs play a key role in regulating skeletal homeostasis through direct and indirect effects on OBs and osteoclasts (1)(2)(3)(4)(5)(6). We previously reported that OB cell number is significantly increased when OBs are co-cultured with MKs in vitro (1,2,4).…”
mentioning
confidence: 99%
“…The alternative ␣ subunit that engages the ␤ 1 subunit for borrelial invasion is not known but, based on known expression profiles of fibroblasts, may be the ␣ 1 , ␣ 2 , ␣ 3 , ␣ 8 , or ␣ 11 subunit (11,15,42,48,83,85). Recently ␣ 3 ␤ 1 -B. burgdorferi interactions were reported for chondrocytes (7,8), and given the abundance of ␣ 3 ␤ 1 in a number of cell types (21,45,49,82), as well as the ability of ␣ 3 ␤ 1 to bind a large number of extracellular matrix proteins, including fibronectin, laminin, and collagen (22,26,88), it is possible that ␣ 3 ␤ 1 may mediate the B. burgdorferi-host cell interaction observed.…”
Section: Discussionmentioning
confidence: 99%
“…We have discussed the role of integrin αvβ3 in the development osteoporosis. Recently Lemieux et al reported the involvement of α3β1 & α5β1 in the development of osteoporosis [207]. They found that these two integrins are expressed on the surface of hematopoietic cell, like megakaryocytes and play a crucial role in the megakaryocyte cell mediated osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%